Long range interaction networks within 3Dpol and the roles they play in picornavirus genome replication and recombination - Watkins, Colleen L., author; Peersen, Olve B., advisor; Cohen, Robert, committee member; Ho, P. Shing, committee member; Wilusz, Jeffrey, committee member (Colorado State University. Libraries, 2020)
Picornaviruses contain a single-stranded positive sense RNA genome approximately 7.5kb in length. The genome encodes for a single polyprotein that can future be divided into three functional regions; the P1 region containing the viral capsid proteins, the P2 region whose proteins function primarily in membrane rearrangement during viral replication, and the P3 region which contains four protein responsible for RNA replication. The final protein in the P3 region is 3Dpol, an RNA-dependent RNA polymerase (RdRP) whose structure is analogous to a "right hand" with fingers, palm and thumb domains, and around which this dissertation will be centered. Section one of this work investigates the roles three regions within the fingers domain play in the catalytic cycle of 3Dpol: "The kink" located within the index finger, "the gateway" found on the pinky, and "the sensor", which bridges the two beta-strands of the middle finger. This study demonstrates that the kink residues are involved in RNA binding as mutations to these residues result in decreased initiation time and elongation complex lifetime. The gateway residues are found to act as a molecular stop against which the template-RNA strand positions itself post-translocation, eventually resetting the active site for the next round of nucleotide incorporation. Lastly the sensor residues serve two key functions: 1) A final checkpoint to determine the correct nucleotide has entered the active site, and 2) As a possible source for proton donation to the pyrophosphate leaving group formed during catalysis. The inter-connected nature of the residues investigated in this section give rise to the idea that it is not individual residues alone that control major steps during the catalytic cycle, but instead that long ranging interaction networks within the different polymerase domains are ultimately responsible for controlling different actions carried out by the polymerase. Section two of this work looks at the long-range interaction networks within 3Dpol by dissecting the roles each polymerase domain plays in catalytic cycle. Through generation of chimeric polymerases it was determined that the pinky finger, with some influence by the fingers domain, controls RNA binding, the palm domain dictates nucleotide discrimination, and nucleotide capture and active site closure rates. It was also established that the thumb domain controls translocation, and an interaction between the palm and thumb domains was needed to generate a viable virus, supporting the idea of interface I, a protein-protein interface that was discovered in the first 3Dpol crystal structure. What is most striking about these findings is that unlike other single subunit polymerases that perform translocation by using a large swinging motion within the fingers domain, viral RdRPs use an entirely different domain altogether. The last section of this work deals with viral recombination, an event that is carried out at a low frequency during virus replication. Recombination is proposed to be a mechanism by which mutations can be purged from the genome independent of polymerase fidelity. This study carries out a mechanistic investigation into how mutation of residue 420 from a leucine to an alanine affects polymerase replication kinetics. It also takes a look at the mutation of residue 64 from a glycine to a serine, a previously identified mutation that results in a high-fidelity polymerase, in the presence and absence of L420A. This work revealed that mutations L420A and G64S operate independently of each other by affecting different steps in the catalytic cycle with G64S increases in fidelity predominately from monitoring nucleosugar positioning while L420A affects nucleobase positioning and polymerase grip on the product RNA strand.
Keywords: picornavirus; virus recombination; enzyme kinetics; virus replication; polymerase